Rancang Bangun Aplikasi Stok Opname Berbasis Website Menggunakan Model Prototype - Al Ahmad, Ubaidillah; Rachman, Andy; Sulistyowati, Sulistyowati Sulistyowati; Sujono, Hari Agus; Sulistyowati, Riny; Alala, Pratama Sandy; Susilowati, Arda Gusema (Institut Teknologi Adhi Tama Surabaya, 2024)
Stock opname is the process of recording goods or logistics, encompassing administrative and operational activities such as receiving, issuing, arranging, and maintaining goods in the warehouse. This activity often takes a long time and can hinder company operations. Based on information from the company, the researcher developed a web-based stock management system. This study designs a web application using the prototype model to display and update stock information at New Central CTCP. The application can speed up the stock name recording process and provide more valid and up-to-date information. Eight respondents tested this application, including the company owner, admin, warehouse manager, and five employees, using the System Usability Scale (SUS), with an average score of 86.25%, indicating that the system is highly useful for New Central CTCP. The application has been implemented and evaluated based on Application Functionality and Application Usability, using the Functionality and Usability Factors from ISO 9126. In terms of Functionality, the application received a score of 92.6%, while in terms of Usability, it received a score of 91.2%.